Gender in The Sustainable Development Goals in Kurdistan Region-Iraq - Dashty Ismail Jamil; Bashdar S. Mawlud (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research will stress the importance of achieving the SDG4 of gender equality as a prerequisite to achieve all the other SDGs, for instance the relationship of girls or women’s education background and other development outcomes like child health and children’s performance at school and its correlation with their mother’s education background in Kurdistan region of Iraq. Primary and secondary data will be used to dive into the girls representation in education and then use the scale to compare with the rest of Iraq and other neighboring countries just to get an insight as to how much progress has been made and how this progress can be scaled on the international list, then I will attempt to draw a correlation between mother’s education and their children’s performances by administering two questionnaires, one for the teachers and the other one is for those women whose their children is at school, the sample size will be more than 150 schools which they will be randomly selected all across Kurdistan Region. The gender issues according to the available data in KRI started to improve in 1992 right after the regional government gained its independence, though after the same year there were some equality issues, but with continues efforts by the ministry of education things started to improve